The comparative analysis of formation and realization investment strategy of the oil and gas enterprises of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The innovative way of development of the branch, defined within GPFIIR as the general direction, assumes need of activization of investment activity of the oil and gas enterprises that, in turn, predetermines importance of formation and realization of investment strategy. However lack of researches in the field of management of investment development of the oil and gas enterprises which would consider system influence of investments is one of the major factors, essentially constraining increase of efficiency of functioning of the oil and gas enterprises.
Keywords: investments; strategic management; oil and gas sector